2001
DOI: 10.3102/00028312038002437
|View full text |Cite
|
Sign up to set email alerts
|

The Classroom Social Environment and Changes in Adolescents’ Motivation and Engagement During Middle School

Abstract: The authors investigated how students’ (N = 233) perceptions of the social environment of their eighth-grade classroom related to changes in motivation and engagement when they moved from seventh to eighth grade. In general, prior motivation and engagement were strong predictors of subsequent motivation and engagement, whereas gender, race, and prior achievement were not related to changes in motivation or engagement. A higher-order classroom social environment factor accounted for significant changes in all m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
630
3
45

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 911 publications
(707 citation statements)
references
References 55 publications
29
630
3
45
Order By: Relevance
“…Some measure engagement as self-regulated learning (e.g., Ryan & Patrick, 2001). Some researchers define engagement in terms of the characteristics of the students' learning environments, such as the quality of classroom dialogue (Nystrand & Gamoran, 1991) or the culture of the college campus (Kuh, 2000).…”
Section: Learning Engagementmentioning
confidence: 99%
“…Some measure engagement as self-regulated learning (e.g., Ryan & Patrick, 2001). Some researchers define engagement in terms of the characteristics of the students' learning environments, such as the quality of classroom dialogue (Nystrand & Gamoran, 1991) or the culture of the college campus (Kuh, 2000).…”
Section: Learning Engagementmentioning
confidence: 99%
“…Given the importance of classroom context for the development of adolescents, and Greek adolescents in particular (because their classmates remain the same throughout their school education), and their Internet use behaviors (Ryan & Patrick, 2001;Festl, Scharkow & Quandt, 2013;Stavropoulos, Kuss, Griffiths & Motti-Stefanidi, 2015), assessing the influence of peer involvement in MMORPGs in relation to IA severity appears important.…”
mentioning
confidence: 99%
“…However, it also leads to deeper levels of learning because in order to build on each other's ideas, the students must first listen and understand the contributions of others students in order to respond or add to it (Hadjioannou, 2007). Additionally, past studies have shown that during discussion students are attentive, active, more engaged, and motivated (see Bligh 2000 for a review; Ryan & Patrick, 2001). …”
Section: The Current Studymentioning
confidence: 99%